2009
DOI: 10.1158/1078-0432.ccr-09-1810
|View full text |Cite
|
Sign up to set email alerts
|

Role of Class 3 Semaphorins and Their Receptors in Tumor Growth and Angiogenesis

Abstract: Class 3 semaphorins (SEMA3) were first identified as glycoproteins that negatively mediate neuronal guidance by binding to neuropilin and repelling neurons away from the source of SEMA3. However, studies have shown that SEMA3s are also secreted by other cell types, including tumor cells, where they play an inhibitory role in tumor growth and angiogenesis (specifically SEMA3B and SEMA3F). SEMA3s primarily inhibit the cell motility and migration of tumor and endothelial cells by inducing collapse of the actin cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 71 publications
6
109
0
1
Order By: Relevance
“…Taken together, these findings suggest that SEMA3A, SEMA3B, and SEMA3F inhibit tumor growth. Although most members of the SEMA3s have been shown to be inhibitory, some promote tumor growth and metastasis (23). For instance, SEMA 3C promotes glomerular endothelial cell proliferation, adhesion, directional migration, and tube formation in vitro (24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that SEMA3A, SEMA3B, and SEMA3F inhibit tumor growth. Although most members of the SEMA3s have been shown to be inhibitory, some promote tumor growth and metastasis (23). For instance, SEMA 3C promotes glomerular endothelial cell proliferation, adhesion, directional migration, and tube formation in vitro (24).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is reported that overexpression of SEMA3G can inhibit breast cancer and melanoma growth and angiogenesis (8,25), its role in the inhibition of invasion and migration has not been reported. Because SEMA3s exert its function by interacting with its receptors neuropilins (NRP) and plexins (23) and SEMA3G receptor NRP2 participates in human glioma progression (26), we designed this study to determine the role of SEMA3G in glioma cell migration and invasion ability. In this study, we generated the SEMA3G stable expressing human glioblastoma U251 (U251MG) cell line and then examined the migratory and invasive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…SEMAs are glycoproteins that were originally described as mediators of neuronal guidance (10,11). Class 3 SEMAs (SEMA3) serve as key regulators of cellular processes, such as cell survival, proliferation, apoptosis, and migration (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Class 3 SEMAs (SEMA3) serve as key regulators of cellular processes, such as cell survival, proliferation, apoptosis, and migration (11,12). Both SEMA3F and SEMA3B are mapped to chromosome 3p21.3, a region of frequent loss in lung, breast, and endometrial cancers (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…NRP1 can enhance the affinity of some VEGF isoforms to bind to VEGF-R2 (23,24). SEMA3s include seven family members; six of them bind to NRP1, NRP2, or to both receptors (25,26). SEMA3s play a dual inhibitory role on tumor angiogenesis and tumor growth.…”
Section: Frequent Deletion Of 3p211 Region Carrying Semaphorin 3g Anmentioning
confidence: 99%